2020
DOI: 10.1161/jaha.119.015133
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Transcatheter Aortic Valve Implantation on Coronary Hemodynamics in Patients With Concomitant Coronary Artery Disease and Severe Aortic Stenosis

Abstract: Background As younger patients are being considered for transcatheter aortic valve implantation (TAVI), the assessment and treatment of concomitant coronary artery disease is taking on increased importance. Methods and Results Thirteen contemporary lower‐risk patients with TAVI with severe aortic stenosis (AS) and moderate‐severe coronary lesions were included. Patients underwent assessment of coronary hemodynamics in the presence of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…In two of these studies, significant improvement in CFR at 6 and 30 months after AVR was mainly attributable to an increase in coronary blood flow during maximal hyperemia, whereas resting coronary flow remained similar before and after TAVR or SAVR, respectively ( 100 , 102 ). The small prospective study by Vendrik et al regarding the longer-term effects of TAVR on invasively measured coronary hemodynamics by dual-sensor (Doppler and pressure) wire revealed an ongoing increase in hyperemic coronary flow as well as in CFR immediately after TAVR and 6 months after the procedure compared with pre-TAVR values ( 103 ). Hyperemic microcirculatory resistance was simultaneously continued to decrease in a similar manner as the CFR increased during 6 months follow-up ( 103 ).…”
Section: Coronary Hemodynamics After Transcatheter Aortic Valve Repla...mentioning
confidence: 99%
“…In two of these studies, significant improvement in CFR at 6 and 30 months after AVR was mainly attributable to an increase in coronary blood flow during maximal hyperemia, whereas resting coronary flow remained similar before and after TAVR or SAVR, respectively ( 100 , 102 ). The small prospective study by Vendrik et al regarding the longer-term effects of TAVR on invasively measured coronary hemodynamics by dual-sensor (Doppler and pressure) wire revealed an ongoing increase in hyperemic coronary flow as well as in CFR immediately after TAVR and 6 months after the procedure compared with pre-TAVR values ( 103 ). Hyperemic microcirculatory resistance was simultaneously continued to decrease in a similar manner as the CFR increased during 6 months follow-up ( 103 ).…”
Section: Coronary Hemodynamics After Transcatheter Aortic Valve Repla...mentioning
confidence: 99%
“…In addition, 15% of these measurements crossed the 0.89 threshold post-AVR, potentially changing the indication for treatment. A few small-sized studies included protracted follow-up measurements at 2, 6, or 12 mo (24,27,28). Again, these studies predominantly demonstrated progressively lower FFR values over time, explained by an incremental increase in hyperemic whole cycle coronary flow but stable iFR and unchanged flow during the wave-free period of diastole.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent, echocardiographic-based study, indexed LV mass decreased from 117 to 100 g/m 2 in a surgical and 114 to 108 g/m 2 in a transcatheter AVR group after 3 mo with further reductions at 1 yr (32). Whether these global changes in LV remodeling translate into improvement of microvascular function and hence might potentially change the absolute values of the FFR and RFR measurements, is not yet known, and available data from small series are not able to provide evidence for these hypotheses (24,28). In this respect, the present study, with 6 mo invasive follow-up, will hopefully provide more insight.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Vendrik et al reported a significant reduction of FFR values over time up to 6 months after TAVI, whereas iFR did not show significant variations at 6 months of follow up [ 44 ]. The authors concluded that using resting indices may be more appropriate to select TAVI candidates who require CAD treatment.…”
Section: Functional Cad Assessment In Aortic Stenosismentioning
confidence: 99%